The Effectiveness of Virtual Patient Simulations in Enhancing‎Medical Education: A Systematic Literature Review with A Fo‎cus on Bahrain and The GCC - Jaber, Fayzeh Abdulkareem; Al-Balasmeh, Hani; Jaber, Nour Abdulkareem; Jaber, Ahmad AbdulKareem; Abdulsattar, Saeed Serwan; Mahmood, Asif (International Journal of Basic and Applied Sciences, 2025)
This systematic literature review assesses the efficacy of Virtual Patient Simulations (VPS) in enhancing essential learning outcomes in ‎medical education, particularly regarding clinical reasoning, communication skills, and information retention. The evaluation, conducted per ‎PRISMA principles, combined information from 18 eligible studies published between 2014 and 2024. The results indicate that VPS ‎significantly improves clinical reasoning (66.7%), communication (44.4%), and information retention (88.9%) relative to conventional techniques. Tutorials, feedback, and debriefing exercises enhance critical thinking and student engagement.‎ The research highlights advanced modalities that augment immersion and student involvement, such as first-person perspectives, natural ‎language processing, and voice input. Despite its promise, current research indicates limitations in generalizability, standardization, and ‎long-term impact evaluation, especially in the GCC context. Institutions like Arabian Gulf University (AGU) in Bahrain now use technology like Body Interact, underscoring the region’s urgent need for culturally tailored VPS solutions. This report provides evidence-based ‎insights for educators, curriculum creators, and policymakers seeking to improve medical teaching using immersive technology in Bahrain and ‎the GCC area‎.